Excess mortality among older adults institutionalized in long-term care facilities during the COVID-19 pandemic: a population-based analysis in Catalonia - Laia Cases; Laia Cases; Emili Vela; Emili Vela; Sebastià J. Santaeugènia Gonzàlez; Sebastià J. Santaeugènia Gonzàlez; Joan Carles Contel; Joan Carles Contel; Joan Carles Contel; Gerard Carot-Sans; Gerard Carot-Sans; Marc Coca; et al. (Frontiers Media S.A., 2023)
ObjectivesTo assess excess mortality among older adults institutionalized in nursing homes within the successive waves of the COVID-19 pandemic in Catalonia (north-east Spain).DesignObservational, retrospective analysis of population-based central healthcare registries.Setting and participantsIndividuals aged >65 years admitted in any nursing home in Catalonia between January 1, 2015, and April 1, 2022.MethodsDeaths reported during the pre-pandemic period (2015-2019) were used to build a reference model for mortality trends (a Poisson model, due to the event counting nature of the variable "mortality"), adjusted by age, sex, and clinical complexity, defined according to the adjusted morbidity groups. Excess mortality was estimated by comparing the observed and model-based expected mortality during the pandemic period (2020-2022). Besides the crude excess mortality, we estimated the standardized mortality rate (SMR) as the ratio of weekly deaths' number observed to the expected deaths' number over the same period.ResultsThe analysis included 175,497 older adults institutionalized (mean 262 days, SD 132), yielding a total of 394,134 person-years: 288,948 person-years within the reference period (2015-2019) and 105,186 within the COVID-19 period (2020-2022). Excess number of deaths in this population was 5,403 in the first wave and 1,313, 111, −182, 498, and 329 in the successive waves. The first wave on March 2020 showed the highest SMR (2.50; 95% CI 2.45-2.56). The corresponding SMR for the 2nd to 6th waves were 1.31 (1.27-1.34), 1.03 (1.00-1.07), 0.93 (0.89-0.97), 1.13 (1.10-1.17), and 1.07 (1.04-1.09). The number of excess deaths following the first wave ranged from 1,313 (2nd wave) to −182 (4th wave). Excess mortality showed similar trends for men and women. Older adults and those with higher comorbidity burden account for higher number of deaths, albeit lower SMRs.ConclusionExcess mortality analysis suggest a higher death toll of the COVID-19 crisis in nursing homes than in other settings. Although crude mortality rates were far higher among older adults and those at higher health risk, younger individuals showed persistently higher SMR, indicating an important death toll of the COVID-19 in these groups of people.